2022
DOI: 10.1038/s41420-022-01179-y
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane induces microRNA-18a to delay rat neurodevelopment via suppression of the RUNX1/Wnt/β-catenin axis

Abstract: Sevoflurane anesthesia is reported to repress neurogenesis of neural stem cells (NSCs), thereby affecting the brain development, but the underlying mechanism of sevoflurane on the proliferation of NSCs remains unclear. Thus, this study aims to discern the relationship between sevoflurane and NSC proliferation. Bioinformatics tools were employed to predict the expression of microRNA-18a (miR-18a) in 9-day-old neonatal rat hippocampal tissues after sevoflurane treatment and the downstream genes of miR-18a, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For example, TTYH3 inhibits apoptosis in CCA through the Wnt/β-catenin signaling pathway [ 30 ]. Furthermore, sevoflurane has been found to function in tumors via the Wnt/β-catenin signaling pathway [ 31 , 32 ]. Recent studies have shown that sevoflurane inhibits the proliferation and invasion of osteosarcoma cells by targeting the miR-203/Wnt/β-Catenin axis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, TTYH3 inhibits apoptosis in CCA through the Wnt/β-catenin signaling pathway [ 30 ]. Furthermore, sevoflurane has been found to function in tumors via the Wnt/β-catenin signaling pathway [ 31 , 32 ]. Recent studies have shown that sevoflurane inhibits the proliferation and invasion of osteosarcoma cells by targeting the miR-203/Wnt/β-Catenin axis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) regulate gene expression through translational repression, or mRNA deadenylation and mRNA decay [ 16 ]. There is growing evidence that miRNAs are associated with neurodevelopment and the development of various psychiatric diseases [ 17 , 18 ]. Overall levels of miRNAs in the prefrontal cortex have been reported to be down-regulated in patients with major depressive disorder following suicide compared to patients who died without psychiatric illness [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) regulate gene expression through translational repression, or mRNA deadenylation and mRNA decay [16]. There is growing evidence that miR-NAs are associated with neurodevelopment and the development of various psychiatric diseases [17,18]. Overall levels of miRNAs in the prefrontal cortex have been reported to be down-regulated in patients with major depressive disorder following suicide compared to patients who died without psychiatric illness [19].…”
Section: Introductionmentioning
confidence: 99%